Evaluating the management of anaphylaxis in US emergency departments: Guidelines vs. practice - Russell, W. Scott (Second Affiliated Hospital of Zhejiang University School of Medicine, 2013)
BACKGROUND: Anaphylaxis is characterized by acute episodes of potentially life-threatening symptoms that are often treated in the emergency setting. Current guidelines recommend: 1) quick diagnosis using standard criteria; 2) first-line treatment with epinephrine; and 3) discharge with a prescription for an epinephrine auto-injector, written instructions regarding long-term management, and a referral (preferably, allergy) for follow-up. However, studies suggest low concordance with guideline recommendations by emergency medicine (EM) providers. The study aimed to evaluate how emergency departments (EDs) in the United States (US) manage anaphylaxis in relation to guideline recommendations. METHODS: This was an online anonymous survey of a random sample of EM health providers in US EDs. RESULTS: Data analysis included 207 EM providers. For respondent EDs, approximately 9% reported using agreed-upon clinical criteria to diagnose anaphylaxis; 42% reported administering epinephrine in the ED for most anaphylaxis episodes; and <50% provided patients with a prescription for an epinephrine auto-injector and/or an allergist referral on discharge. Most provided some written materials, and follow-up with a primary care clinician was recommended. CONCLUSIONS: This is the first cross-sectional survey to provide “real-world” data showing that practice in US EDs is discordant with current guideline recommendations for the diagnosis, treatment, and follow-up of patients with anaphylaxis. The primary gaps are low (or no) utilization of standard criteria for defining anaphylaxis and inconsistent use of epinephrine. Prospective research is recommended.